2008
DOI: 10.1039/b719033f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular simulation study of temperature effect on ionic hydration in carbon nanotubes

Abstract: Molecular dynamics simulations have been performed to investigate the hydration of Li(+), Na(+), K(+), F(-), and Cl(-) inside the carbon nanotubes at temperatures ranging from 298 to 683 K. The structural characteristics of the coordination shells of ions are studied, including the ion-oxygen radial distribution functions, the coordination numbers, and the orientation distributions of the water molecules. Simulation results show that the first coordination shells of the five ions still exist in the nanoscale c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 48 publications
6
68
0
Order By: Relevance
“…We can find that, for the three cations, their distributions of cos˛present maxima at −1, indicating that the water molecules around a cation tend to have their oxygen atoms pointing to the cation. This observation is consistent with the previous results [14,15]. The values at −1 can reflect the orientation strength of the ionic hydration.…”
Section: Orientation Distributions Of Water Molecules In the First Cosupporting
confidence: 92%
See 3 more Smart Citations
“…We can find that, for the three cations, their distributions of cos˛present maxima at −1, indicating that the water molecules around a cation tend to have their oxygen atoms pointing to the cation. This observation is consistent with the previous results [14,15]. The values at −1 can reflect the orientation strength of the ionic hydration.…”
Section: Orientation Distributions Of Water Molecules In the First Cosupporting
confidence: 92%
“…2, because of the confinement effect of the CNTs, the values of the cation-oxygen RDFs turn to zero as r increases, which is consistent with the observations of previous simulations [14,15]. In Fig.…”
Section: Radial Distribution Functions Of Cation-water In Cntssupporting
confidence: 91%
See 2 more Smart Citations
“…Although a few theoretical works on TiO 2 are related to water [15][16][17][18], few have been focused on the diffusion of water confined in TiO 2 slits. Our previous works of molecular dynamics (MD) showed that the chemical modification of carbon nanotubes would affect the water behaviors [19][20][21][22][23]. It means that the chemical property of the solid surface plays an important role in the structural behaviors of confined water, and will accordingly influence their diffusion behavior.…”
mentioning
confidence: 99%